Model Model-Based Construction Understanding and implementation challenges - A Case study - Ahmad, Meqdad; Nasr, Khalid (My University, 2025)
This study explores the challenges experienced in the implementation of Model Based Construction (MBC) and examines how different stakeholders understand and approach the concept. The empirical work draws on a literature review and a case study of Kaj 16, an ongoing project in Sweden that is implementing model based construction. Using a qualitative approach with semi-structured interviews and document analysis, the research investigates how stakeholders interpret MBC, the organizational and technical barriers they face, and the strategies developed to overcome them. The findings show that implementing MBC represents a significant shift in the construction sector, as it extends the use of BIM from design into site practices. The study highlights differences in how MBC is understood and reveals that full implementation has not yet been achieved due to multiple barriers spanning organizational, technical, legal, and financial domains. Addressing these challenges—supported by early standardization and strong client leadership—is essential to enable successful and complete adoption of MBC.
Keywords: Model-Based Construction (MBC); Building Information Modelling (BIM); Digital Transformation; MBC Implementation Challenges; Construction Process Improvement